Biocontrol-Based Integrated Management of Oilseed Rape Pests - Williams, Ingrid H.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2010)
Oilseed rape is a major arable crop in both Europe and North America. It is attacked by unique complexes of insect pests still largely controlled through the application of chemical insecticides. Crop management systems for the future must combine sustainability with environmental acceptability to satisfy both social and economic demands. This book, in its 17 chapters each led by a world expert, reviews research progress towards developing integrated pest management systems for the crop that enhance conservation biocontrol. This approach is particularly timely because of the development in Europe of insecticide resistance in the pollen beetle, a major pest of the crop. The past decade has seen considerable progress in our knowledge of the parasitoids and predators that contribute to biocontrol, of their distribution patterns, and their behavioural ecology, both within and without the crop. There is potential for natural enemy conservation through modification of within-field crop husbandry practices, as well as, on the landscape scale, through habitat manipulation to encourage vegetational diversity. This book will prove invaluable as a text for researchers, university teachers, graduate scientists, extension workers and growers involved in integrated pest management.
The Major Insect Pests of Oilseed Rape in Europe and Their Management: An Overview -- Parasitoids of Oilseed Rape Pests in Europe: Key Species for Conservation Biocontrol -- Key Parasitoids of the Pests of Oilseed Rape in Europe: A Guide to Their Identification -- Ground Beetles as Predators of Oilseed Rape Pests: Incidence, Spatio-Temporal Distributions and Feeding -- Pests and Their Enemies in Spring Oilseed Rape in Europe and Challenges to Integrated Pest Management -- Key Pests and Parasitoids of Oilseed Rape or Canola in North America and the Importance of Parasitoids in Integrated Management -- Crop Location by Oilseed Rape Pests and Host Location by Their Parasitoids -- Spatio-Temporal Distributions of Pests and Their Parasitoids on the Oilseed Rape Crop -- Biological Rape Pest Control in Spatio-Temporally Changing Landscapes -- Insect Pests and Spiders in Oilseed Rape and Their Response to Site and Landscape Factors -- Impact of Soil Tillage on Parasitoids of Oilseed Rape Pests -- Chemical Control of Insect Pests and Insecticide Resistance in Oilseed Rape -- Impact of Insecticides on Parasitoids of Oilseed Rape Pests -- Oilseed Rape, Bees and Integrated Pest Management -- The proPlant Decision Support System: Phenological Models for the Major Pests of Oilseed Rape and Their Key Parasitoids in Europe -- Farming Systems, Integrated Crop Management and Winter Oilseed Rape Production -- Integrating Crop and Landscape Management into New Crop Protection Strategies to Enhance Biological Control of Oilseed Rape Insect Pests.
Keywords: Life sciences; Agriculture; Ecology; Plant diseases; Invertebrates; Life Sciences; Agriculture; Plant Pathology; Invertebrates; Ecology